Α-RgIB: A Novel Antagonist Peptide of Neuronal Acetylcholine Receptor Isolated from Conus regius Venom. (27th February 2013) - Braga, Maria Cristina Vianna; Nery, Arthur Andrade; Ulrich, Henning; Konno, Katsuhiro; Sciani, Juliana Mozer; Pimenta, Daniel Carvalho
Abstract : Conus venoms are rich sources of biologically active peptides that act specifically on ionic channels and metabotropic receptors present at the neuromuscular junction, efficiently paralyzing the prey. Each species of Conus may have 50 to 200 uncharacterized bioactive peptides with pharmacological interest. Conus regius is a vermivorous species that inhabits Northeastern Brazilian tropical waters. In this work, we characterized one peptide with activity on neuronal acetylcholine receptor (nAChR). Crude venom was purified by reverse-phase HPLC and selected fractions were screened and sequenced by mass spectrometry, MALDI-ToF, and ESI-Q-ToF, respectively. A new peptide was identified, bearing two disulfide bridges. The novel 2, 701 Da peptide belongs to the cysteine framework I, corresponding to the cysteine pattern CC-C-C. The biological activity of the purified peptide was tested by intracranial injection in mice, and it was observed that high concentrations induced hyperactivity in the animals, whereas lower doses caused breathing difficulty. The activity of this peptide was assayed in patch-clamp experiments, on nAChR-rich cells, in whole-cell configuration. The peptide blocked slow rise-time neuronal receptors, probably α 3 β 4 and/or α 3 β 4 α 5 subtype. According to the nomenclature, the new peptide was designated as α -RgIB.